MTF-1-mediated repression of the zinc transporter Zip10 is alleviated by zinc restriction. - Louis A Lichten (Public Library of Science (PLoS), 2011)
The regulation of cellular zinc uptake is a key process in the overall mechanism governing mammalian zinc homeostasis and how zinc participates in cellular functions. We analyzed the zinc transporters of the Zip family in both the brain and liver of zinc-deficient animals and found a large, significant increase in Zip10 expression. Additionally, Zip10 expression decreased in response to zinc repletion. Moreover, isolated mouse hepatocytes, AML12 hepatocytes, and Neuro 2A cells also respond differentially to zinc availability in vitro. Measurement of Zip10 hnRNA and actinomycin D inhibition studies indicate that Zip10 was transcriptionally regulated by zinc deficiency. Through luciferase promoter constructs and ChIP analysis, binding of MTF-1 to a metal response element located 17 bp downstream of the transcription start site was shown to be necessary for zinc-induced repression of Zip10. Furthermore, zinc-activated MTF-1 causes down-regulation of Zip10 transcription by physically blocking Pol II movement through the gene. Lastly, ZIP10 is localized to the plasma membrane of hepatocytes and neuro 2A cells. Collectively, these results reveal a novel repressive role for MTF-1 in the regulation of the Zip10 zinc transporter expression by pausing Pol II transcription. ZIP10 may have roles in control of zinc homeostasis in specific sites particularly those of the brain and liver. Within that context ZIP10 may act as an important survival mechanism during periods of zinc inadequacy.